Automated Methodology for Volume Fraction Measurement of Three Phase Steel Micrograph Using Image Processing Techniques - Banerjee, Siddhartha (Iraqi Journal of Science, 2022)
A quantitative description of microstructure governs the characteristics of the material. Various heat and excellent treatments reveal micro-structures when the material is prepared. Depending on the microstructure, mechanical properties like hardness, ductility, strength, toughness, corrosion resistance, etc., also vary. Microstructures are characterized by morphological features like volume fraction of different phases, particle size, etc. Relative volume fractions of the phases must be known to correlate with the mechanical properties. In this work, using image processing techniques, an automated scheme was presented to calculate relative volume fractions of the phases, namely Ferrite, Martensite, and Bainite, present in the microscopic image of high strength low alloy steel. First, the microscopic image was segmented into Ferrite, Martensite, and Bainite regions. The phase structure's geometric property was used to identify different phases present inside the micrograph. After phase detection, the volume fraction of each region is calculated.